The Influence of Entrepreneurship in the Higher Education Environment on Entrepreneurial Motivation - Sattar Rasul; Henny Purnama Dewi; Atika Aini Nasution; Irma Herliza Rizki; Bambang Sutejo (International Journal of Advanced Research, 2024)
This study aims to analyze the influence of entrepreneurship in the university environment on students' entrepreneurial motivation. Along with the increasingly rapid economic development, entrepreneurship has become an attractive career choice for the younger generation, especially students. Universities as educational institutions have a strategic role in shaping the character and entrepreneurial mindset of students through the entrepreneurship programs they organize. This study uses a quantitative approach with survey methods and multiple regression analysis to identify factors that influence entrepreneurial motivation. The results of the study show that entrepreneurship in universities, which include entrepreneurship courses, seminars, training, and business incubators, have a significant influence on increasing students' entrepreneurial motivation. These entrepreneurship programs provide knowledge, skills, and support that are very important for students to start their businesses. In addition, social support from family and friends as well as economic conditions also play a role in increasing students' entrepreneurial motivation. The conclusion of this study is that entrepreneurship in universities contributes positively to encouraging students to enter the business world, so universities need to continue to develop their entrepreneurship programs to support the creation of innovative and competitive young entrepreneurs.